General geology and relationship between particle size, plasticity index and clay mineral content with slope failure at Kampung Slow Pok Long, Dabong, Kelantan. - Sitresh A/L Latchmanan (2016)
A study was conducted around the area of Kampung Slow Pok Long, Dabong, Kelantan to determine the general geology around the study area, particle size distribution, plastic limit, liquid limit, plasticity index, and clay mineral content of soils from failed slopes. The objective was to produce an updated geological map of the study area and to determine if these parameters inﬂuenced the slope failures. 21 samples were collected at every failed slope. The study area is dominated with undulating and hilly topography and the geology of the area consists of limestone, phyllite and interbedding of siltstone and shale. The sieving results shows that most samples collected are dominated by sands to gravel and most samples are medium plastic in naure. The results show that the plastic limit and liquid limit as well as plasticity index are not inﬂuenced by particle size distribution. However, the occurance of clay minerals such as kaolinite, illite and montmorillonite tend to inﬂuence the plasticity indices, and contribute towards making the slope unstable.